2024
DOI: 10.3389/fimmu.2024.1306059
|View full text |Cite
|
Sign up to set email alerts
|

Association of composite dietary antioxidant index with prevalence of stroke: insights from NHANES 1999-2018

Tian-Qi Teng,
Jing Liu,
Fang-Fang Hu
et al.

Abstract: BackgroundThere is a growing acknowledgment of the potential influence of antioxidative effects resulting from dietary decisions on the occurrence of stroke. The objective of this study was to elucidate the correlation between the composite dietary antioxidant index (CDAI) and the incidence of stroke in the general population of the United States.MethodsWe gathered cross-sectional data encompassing 40,320 participants from the National Health and Nutrition Examination Survey (NHANES) spanning the years 1999 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…Notably, in those with a BMI under 25, the link between CDAI and stroke does not hold statistical significance. This observation aligns with findings from Teng et al and Mao et al, though their research did not delve into BMI’s role in the CDAI-stroke relationship ( 12 , 13 ). Considering the differences in variable adjustments mentioned earlier, it becomes essential to undertake more extensive adjustments of variables to further examine the interaction between CDAI and BMI in stroke risk among American adults.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Notably, in those with a BMI under 25, the link between CDAI and stroke does not hold statistical significance. This observation aligns with findings from Teng et al and Mao et al, though their research did not delve into BMI’s role in the CDAI-stroke relationship ( 12 , 13 ). Considering the differences in variable adjustments mentioned earlier, it becomes essential to undertake more extensive adjustments of variables to further examine the interaction between CDAI and BMI in stroke risk among American adults.…”
Section: Discussionsupporting
confidence: 89%
“…These findings collectively affirm the link between higher dietary antioxidant intake and reduced stroke risk. Teng et al ( 13 ) also found that higher CDAI scores were associated with a lower stroke risk after adjusting for confounders, with an OR of 0.96 (95% CI 0.94–0.98, p < 0.001), and that nomogram models based on antioxidant intake exhibited substantial predictive power for stroke risk, showing an area under the curve (AUC) of 77.4% (76.3–78.5%). Together, these results support the hypothesis that increased dietary antioxidant intake is associated with a diminished risk of stroke, as evidenced by the CDAI.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations